Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1001/archopht.121.10.1430
|View full text |Cite
|
Sign up to set email alerts
|

A Population-Based Study of the Refractive Outcome in 10-Year-Old Preterm and Full-Term Children

Abstract: To evaluate the refractive outcome in 10year-old prematurely born children and in full-term control children. Methods: Retinoscopy during cycloplegia was performed in 213 prematurely born children from a previous population-based study on the incidence of retinopathy of prematurity and in 217 children born at term. The spherical equivalent, astigmatism, anisometropia, and significant refractive errors (defined as hypermetropia Ͼ3 diopters [D], myopia Յ−1 D, astigmatism Ն1 D in 1 or both eyes, and/or anisometro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
98
4
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 127 publications
(115 citation statements)
references
References 72 publications
(27 reference statements)
7
98
4
3
Order By: Relevance
“…These results are better than most previous longterm reports on prematurely born children, which have shown higher frequencies of refractive errors both in myopic and hypermetropic directions (Fledelius 1996b;Larsson et al 2003;Nissenkorn et al 1983;Quinn et al 1992). The frequency of clinically significant astigmatism (21%) was clearly higher than among children born at term (4-9%) (Atkinson et al 1980), but similar to the figure reported on 10-year-old Swedish children with BW <1500 g (Larsson et al 2003).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…These results are better than most previous longterm reports on prematurely born children, which have shown higher frequencies of refractive errors both in myopic and hypermetropic directions (Fledelius 1996b;Larsson et al 2003;Nissenkorn et al 1983;Quinn et al 1992). The frequency of clinically significant astigmatism (21%) was clearly higher than among children born at term (4-9%) (Atkinson et al 1980), but similar to the figure reported on 10-year-old Swedish children with BW <1500 g (Larsson et al 2003).…”
Section: Discussionsupporting
confidence: 59%
“…From a global perspective, this condition is also one of the leading causes of childhood blindness (Rahi & Gilbert 2005). However, also among those who survive without severe ROP, several studies show that the frequency of other and less severe, long-term ocular and visual complications is increased (Fledelius 1996a,b,c;Darlow et al 1997;Larsson et al 2003Larsson et al , 2005Cooke et al 2004;Holmstro¨m & Larsson 2008;Lindqvist et al 2007Lindqvist et al , 2008Hellgren et al 2007). These studies document a higher rate of refractive errors, strabismus, subnormal visual acuity, reduced contrast sensitivity, visual field defects, oculomotor problems and visuo-perceptive defects at school age and in adolescence in prematurely born children compared with children born at term.…”
Section: Introductionmentioning
confidence: 99%
“…This was very similar to our findings, where we noticed that myopia and astigmatism were more common in prematurely born children than in those born at term. In comparison with the Swedish population-based study (11), our findings were quite similar. The difference was that we did not distinguish significant and high myopia as they did, we evaluated significant hypermetropia as ≥2D, not as the Swedish study ≥3D, either children's age differed at the examination.…”
Section: Discussionsupporting
confidence: 79%
“…The preterm and fullterm children groups were born in the same period and in the same geographical area, and were examined in exactly the same way, what warranted exact comparison between the groups. A comparison of the refractive data from our study with those of other studies (11,7,28,14) is quite difficult because those studies differ in their methods and epidemiological features.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation